Der Coupon-Handelsansatz als Modell für eine subjektbezogene Finanzierung der Kinderbetreuung - Henrik Egbert; Andreas Hildenbrand (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
Abstract: Improving child care and pre-school education is one of the challenging duties of public authorities in Germany. Given the public resources spent on nursery schools, the quantity as well as the quality of early childhood education in Germany is comparatively low. We think that inefficiency is caused by the prevalent object-based financing structure. In this article we present a model for a subject-based financing structure with tradable coupons. The model shows that by introducing tradable coupons a more efficient allocation of resources is possible. Further, the model indicates that tradable coupons also improve the quality of early childhood education.
Keywords: D40; D61; 330; Kinderbetreuung; subjektbezogene Finanzierung; Gutscheine; Coupon-Handelsansatz; Kinderbetreuung; Finanzierung; Voucher; Deutschland